Procuring complex performance : studies of innovation in product-service management - Caldwell, Nigel, 1960-; Howard, Mickey, 1967- (Routledge studies in business organization and networks, 2011)
This book examines the management of Procuring Complex Performance (PCP) in large-scale programmes that includes the downstream support phase in sectors such as construction, healthcare, transport, aerospace, marine and defence. It brings together a series of edited chapters to explain why the traditional combination of linear project management and highly detailed contracts are now unsuited to the dynamics of emerging customer requirements based on performance and outcome. Working with leading business professors across the UK and Europe, Caldwell and Howard present the case for why large-